Hegemoni Amerika Pasca 11/9: Menuju Sebuah 'Imperium Amerika Baru'? - Nur Rachmat Yuliantoro (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Post-9/11 American foreign policy has been viewed by many as, if anything, reactualising American grand strategy to form a 'new American Empire'. This is arguably the greatest ideal long imagined by some groups of 'flea-conservatives' that dominating Bush's foreign policy. These groups believe that the United States, supported by its military and economic supremacy, is the uncontested 'leader' of today's world. Their belief has of course been contested by those scholars who argue that building an 'empire' would only weaken – some even say 'destroy' – U.S. dominant position in international relatiohs. This essay tries to describe in brief both groups' arguments, while also stressing that the first choice of imperial hegemony is the worst not only for the U.S., but also for the international community.